Influence of the Growth Regulators Kinetin and 2,4-D on the Growth of Two Chlorophyte Microalgae, Haematococcus pluvialis and Dunaliella salina - Maria Filomena de Jesus Raposo ,; Rui Manuel Santos Costa de Morais, (Journal of Basic & Applied Sciences, 2013)
Haematococcus pluvialis Flotow and Dunaliella salina Teodoresco are commercially important because of their ability to accumulate very high carotenoid contents. However, their use is hindered by their slow growth rates. This paper reports a study on the effects of two growth regulators, 2,4-D (2,4-dichlorophenoxyacetic acid) and kin (kinetin), in concentrations of 0, 0.5, 1.0 and 2.0 mg l-1 each in a factorial design (24 combinations), as a possible means of enhancing the growth rates. After 12-13 days of treatment with plant hormones, D. salina showed a significant increase in growth with all the hormone concentrations and combinations used and under 15% salinity (NaCl, w/v), (except for 0.5 mg l-12,4-D and no kin), with up to 410% more cells than the control; under 10% salinity (NaCl, w/v), the increase in growth was significant with 0.5 mg l-1 2,4-D and no kin (180% more cells than the control), and also with 1.0 mg l-1 2,4-D and no kin (126% more cells than the control) and 2.0 mg l-1 2,4-D and 0.5 mg l-1 kin (134% more cells than the control) in the culture medium. Cultures of H. pluvialis were significantly influenced under 1.0 mg l-1 2,4-D (with 320% more cells than the control), but alsoshowed a significant increase in the growth rate when the ratio auxin to cytokinin was 1 (equal concentrations of 1.0 mg l-1 of both growth regulators) with more than 290% cells than the control, and with 0.5 mg l-1 2,4-D and 2.0 mg l-1 kin (200% more cells than the control) in the culture medium.